2005
DOI: 10.1002/jcp.20504
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of micron‐scale membrane sub‐domains in live murine sperm

Abstract: Lipid rafts, membrane sub-domains enriched in sterols and sphingolipids, are controversial because demonstrations of rafts have often utilized fixed cells. We showed in living sperm that the ganglioside G(M1) localized to a micron-scale membrane sub-domain in the plasma membrane overlying the acrosome. We investigated four models proposed for membrane sub-domain maintenance. G(M1) segregation was maintained in live sperm incubated under non-capacitating conditions, and after sterol efflux, a membrane alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
93
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 46 publications
16
93
1
1
Order By: Relevance
“…One likely difference among these studies could be the fixation procedure [60], which might affect viability. In fact, it has been reported that GM1 moves rapidly from its position overlying the acrosome to the post-acrosomal area after cell death in unfixed or lightly fixed samples [59]. Our results show that GM1 is located at the postacrosomal region and tail of all ram spermatozoa.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…One likely difference among these studies could be the fixation procedure [60], which might affect viability. In fact, it has been reported that GM1 moves rapidly from its position overlying the acrosome to the post-acrosomal area after cell death in unfixed or lightly fixed samples [59]. Our results show that GM1 is located at the postacrosomal region and tail of all ram spermatozoa.…”
Section: Discussionsupporting
confidence: 49%
“…Nevertheless, the reported results about the location of GM1 in sperm are contradictory. GM1 has been found at the postacrosome of epididymal mouse [57] and rat [58] spermatozoa, and at the acrosomal area of epididymal murine sperm [59]. Conversely, GM1 was reported as nonexistent or patchy and inconsistent throughout the whole sperm cell of human and boar .…”
Section: Discussionmentioning
confidence: 98%
“…Albeit, it is currently not known this may be due to various and possibly complex tasks of MUPP1 in neurons and different subcellular localizations (Suzuki, 2002), whereas in mammalian spermatozoa, MUPP1 action may be limited to one of the few hallmarks of sperm function. DRM rafts, which have been found in mammalian sperm cells of several species (Travis et al, 2001;Trevino et al, 2001;Cross, 2004;Shadan et al, 2004;Sleight et al, 2005;van Gestel et al, 2005;Selvaraj et al, 2006;Thaler et al, 2006), are specifically enriched in cholesterol (Rajendran and Simons, 2005), and, thus, are particularly important during the posttesticular developmental process of capacitation, which is characterized by a net loss of cholesterol . The experimental approaches used in the present study to determine whether capacitation-dependent reorganization of plasma membrane microdomains (van Gestel et al, 2005) is accomplished by a shift of MUPP1 to other subcellular compartments, led to the key observation that, upon capacitation, MUPP1 was still associated with highly-ordered DRM subdomains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it provides evidence for the existence of membrane sub-domains in living cells, which is still a matter of some controversy (Munro, 2003). Standing in contrast to reports on the segregation of GM1 in live sperm (Selvaraj et al, 2006) are studies suggesting that there is no barrier to the lateral diffusion of lipids in mature spermatozoa (Mackie et al, 2001).…”
Section: Gangliosides In Mouse Ovulation and Spermatogenesismentioning
confidence: 99%